Four new species of the genus Tumicla Wallengren, 1863 (Lepidoptera: Erebidae: Arctiinae: Lithosiini) - Volynkin, Anton V.; László, Gyula M. (Zootaxa, 2019)
The present paper contains descriptions of four new species of the genus Tumicla Wallengren, 1863: T. elephantina sp. nov. (South Mozambique), T. mbeghai sp. nov. (NE Tanzania), T. admiranda sp. nov. (SE Democratic Republic of the Congo) and T. smithi sp. nov. (Central Zambia). The male paratype specimen of T. doa Kühne 2007 is proved to be not conspecific with the holotype female but belongs to an undescribed species described here as T. mbeghai sp. nov. rendering Tumicla doa to be known by the female holotype only. Adults, male and female genitalia of the new and related species are illustrated.